Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.3 - Introduction to Polynomials - Exercise Set - Page 366: 55



Work Step by Step

$5x^{2}y+6xy^{2}-5yx^{2}+4-9y^{2}x$ Rewrite the expression putting all the $x$'s first in every term: $5x^{2}y+6xy^{2}-5x^{2}y+4-9xy^{2}=...$ Simplify by combining like terms: $...=(5-5)x^{2}y+(6-9)xy^{2}+4=...$ $...=(0)x^{2}y-3xy^{2}+4=...$ $...=4-3xy^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.